EVALUATION OF THE EFFICIENCY OF ECONOMIC POLICY UNDER THE EUROPE-2020 STRATEGY IN SMALL EUROPEAN UNION COUNTRIES - Banelienė, Rūta (Ekonomika, 2013)
Abstract. The evaluation criteria to measure the efficiency of a state’s economic policy in terms of integration processes in the European Union were determined in the Europe 2020 Strategy endorsed by the European Council in June 2010. According to the Strategy, the European Union has committed to seek progress in the fields of employment, investment in R&D, climate change and energy, education, and poverty reduction. With a view to assessing the economic impact of the above commitments by the European Union vis-a-vis small European Union countries, this article provides an evaluation of the three objectives of the Europe 2020 Strategy – employment, education, and investment in R&D – and their impact on the economic growth in smaller countries of the European Union. This article concludes that many of the smaller European Union countries choose not to be ambitious enough in their national objectives of employment, education, and investment in R&D areas under the Europe 2020 Strategy and, during the 2011–2020 period, they show on average a 4.8% lower annual GDP growth than it could potentially be, i.e. they abandon far-reaching ambitious targets. Key words: economic policy, small European Union countries, Europe 2020 Strategy, employment, education, R&D